Ekonomi Berbagi dan Disrupsi Pasar Transportasi di Indonesia: Kajian Literatur atas Peran Transportasi Online dalam Transformasi Ekonomi - Galih Adi Sulistyo; Maudhy Satyadharma (Journal of Economic and Business Advancement, 2025)
This study aims to analyze the role of online transportation in the context of the sharing economy and its impact on economic and social transformation in Indonesia. The method used is a literature review with a narrative approach that integrates empirical research results from various national and international indexed sources. The results of the study show that online transportation, through platforms such as Gojek, Grab, and Maxim, has created new jobs, increased digital inclusion, and expanded the participation of low-income communities in the digital economy. On the other hand, the disruption caused has put pressure on the conventional transportation sector due to a shift in consumer preferences towards fast, efficient, and transparent services. The adaptation of traditional players through digital collaboration and government policies is a key factor in maintaining the balance of the national transportation ecosystem. The overall results show that online transportation functions not only as an instrument of mobility but also as a catalyst for socio-economic transformation that drives inclusive growth, community empowerment, and the formation of new technology-based interaction patterns in the era of Indonesia's digital economy